Integrated physiological, transcriptomic, and metabolomic analyses of Chrysanthemum ‘Boju’ under excessive indole-3-acetic acid stress - Wang, Yuqing; Duan, Yingying; Chen, Na; Ding, Wanyue; Liu, Yaowu; Xing, Shihai (Frontiers in Plant Science, 2025)
IntroductionIndole-3-acetic acid (IAA) is a key plant hormone involved in regulating development and responses to abiotic stress. However, excessive IAA treatment can induce oxidative stress, impair growth, and potentially lead to plant death. This study investigates the effects of excessive IAA exposure on the growth of Chrysanthemum morifolium (Boju), focusing on the underlying molecular mechanisms.MethodsWe treated C. morifolium with 10 mg/L IAA for nine consecutive days. The impact of this treatment was assessed from various perspectives, including physiological (chlorophyll, carotenoids, and MDA content), biochemical (antioxidant enzyme activities), and molecular (transcriptomic and metabolomic analyses).ResultsIAA treatment significantly increased chlorophyll a, chlorophyll b, and carotenoid levels by 37%, 46%, and 25%, respectively, compared to pre-treatment levels, suggesting that C. morifolium was experiencing stress. Additionally, the malondialdehyde (MDA) content was 1.79 times higher than pre-treatment levels, confirming oxidative stress. To combat this, the plant enhanced its antioxidant defense mechanisms, as shown by a 93.8% increase in peroxidase (POD) activity and a 45% increase in superoxide dismutase (SOD) activity. Exogenous IAA treatment also led to a significant reduction in endogenous hormone levels, including gibberellins (GA3 and GA4), abscisic acid (ABA), and IAA, with decreases of 93%, 45%, 99%, and 99%, respectively.Transcriptomic and metabolomic analyses identified 263 differentially expressed metabolites and 144 differentially expressed genes.DiscussionThese results suggest that C. morifolium is experiencing stress under prolonged IAA treatment and likely limits its growth by reducing endogenous hormone levels to mitigate oxidative stress. The transcriptomic and metabolomic results showed the upregulation of stress-related genes, including proB (Glutamate 5-kinase), proA (Glutamate-5-semialdehyde dehydrogenase), GAD (Glutamate decarboxylase), and peroxidases, alongside the downregulation of PK (Pyruvate kinase), indicateing a complex response involving the regulation of amino acid biosynthesis, coumaric acid metabolism, starch and sucrose metabolism, and pyruvate metabolism. This study highlights the nonlinear effects of IAA on plant growth and stress responses, emphasizing the intricate molecular mechanisms involved in coping with excessive IAA-induced stress.